THE ROLE OF HEALTH WORKERS AND SUPPORT SYSTEM COUNSELORS FOR WOMEN WITH PRIMARY INFERTILITY - Dewi Puspitaningrum; Mohammad Zen Rahfiludin; Zahroh Shaluhiyah; Sri Winarni (Universitas Airlangga, 2022)
Background: Primary infertility is a problem, one of which is psychological in infertile women. Based on the Indonesian In Vitro Fertilization Association (Perfitri), the total cycle of IVF programs in Indonesia in 2021 reached 10,000, the most significant number in handling fertility problems. Problems appear because there are no psychological services. Aims: To explore the role of health workers and counselors in the support system at the central hospital in Semarang for women with primary infertility Methods: This is descriptive research with qualitative exploratory design at the Central Hospital in Semarang City with five health workers and two counselors. The researcher used semi-structured, one-on-one interviews for one week. The data was then analyzed using inductive thematic analysis Results: The results found that the support system for women with primary infertility, from the opinion of health workers, will focus on clinical care and counseling according to the diagnosis from the counselors that women with primary infertility need psychological support to assist the success of clinical care Conclusion: Health workers and counselors need an integrated support system service for women with primary infertility.